Induced phenological avoidance: A neglected defense mechanism against seed predation in plants. (26th December 2019) - Sercu, Bram K.; Moeneclaey, Iris; Bonte, Dries; Baeten, Lander
Abstract: Flowering phenology is an important life‐history trait affecting plant reproductive performance and is influenced by various abiotic and biotic factors. Pre‐dispersal seed predation and pollination are expected to impose counteracting selection pressure on flowering phenology, with pre‐dispersal seed predation expected to favour off‐peak flowering and pollination to favour synchronous flowering. Here we studied the effect of pre‐dispersal seed predation by the beetle Byturus ochraceus, a specialist seed herbivore, on the flowering phenology of Geum urbanum . This forest understorey plant species is self‐pollinating, so that the influence of seed predation can be studied independent from pollination. We measured in detail the timing and predation rate of individual flowers during two consecutive years in more than 60 individuals. We tested the hypotheses that pre‐dispersal seed predation exerts selection for within‐season compensatory flowering as well as for induced phenological avoidance in the following season. We found no indication for compensatory flowering within a growing season, but plants that experienced predation shifted their flowers to the end of the flowering season the subsequent year. This induced phenological avoidance points to a plastic response to pre‐dispersal seed predation that may be adaptive. Importantly, the delay in flower production came at a cost, since flowers later in the season had a reduced seed output, presumably because of increasing light limitation following forest canopy closure. Synthesis . Herbivory by specialist enemies can cause serious fitness decline in hosts. We here show that induced shifts in phenology can form an important defense strategy against pre‐dispersal seed predation. The induced mismatches between herbivore and host phenology are anticipated to be adaptive when herbivory is predictable across successive flowering periods. Abstract : Herbivory by specialist enemies can cause serious fitness decline in hosts. We here show that induced shifts in phenology can form an important defense strategy against pre‐dispersal seed predation. The induced mismatches between herbivore and host phenology are anticipated to be adaptive when herbivory is predictable across successive flowering periods.